Some issues about women who file for divorce in Aceh - Nisa, Haiyun; Koentjoro, Koentjoro (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
Studies on women who file for divorce in Aceh still need to be carried out to get an overview of the current problems and issues related to women who are filing for divorce. The problems experienced by women include conflicts in the household that encourage them to file a lawsuit to the Syar'iyah Court/Mahkamah until they get a permanent decision and have legal force from the judiciary. Even after divorce, women still face various obstacles to achieve happiness. This study aims to provide an overview of the current issues of women seeking divorce in Aceh. The research data are from observations and practical experience of researchers as professionals in women's and child protection service institutions and psychological service institutions. This study focuses on the psychological aspects experienced by women in stressful situations due to the end of the marital relationship. The results of the thematic data analysis show that the important issues related to women who file for divorce are; an increase in the divorce rate which requires the attention of the parties in an effort to reduce the divorce rate; the legal process in the Religious Courts/Syar'iyah Courts with therapeutic nuances; psychological dynamics of women who are suing for divorce which have an impact on the order of their lives so that they require intervention efforts, including empowerment in economic, psychological, and social aspects. The results of this study are expected to provide recommendations for all parties, including the government, village officials, private institutions, the general public and philanthropy, to seriously pay attention to women who file for divorce so as to minimize the negative impact of divorce on women and children.